(untitled) (GnosisWisdom, 2023)
Introduction Patients with mild or severe Covid-19 do not fully recover and have a wide variety of chronic symptoms for weeks or months after infection, often of a physical, mental and/or social nature. Objective To determine the relationship that exists between clinical-epidemiological characteristics and current health status in patients who presented Covid-19 infection according to the population demanded at the first level of care Methods A quantitative study was carried out, descriptive level, with a non-experimental, transectional, descriptive-correlational design. The sample includes patients who presented infection by Sars-CoV-2 (Covid-19) (n=118). For data collection, the documentary content analysis technique was applied with the instrument, document analysis format. The Nottingham Health Profile Scale (NHP) instrument was applied. Validity and reliability in Great Britain Hunt SM et al. (1985). Results 47.5% of patients who presented infection by Sars-CoV-2 (Covid-19) at the first level of care presented a moderate clinical picture and a moderate current physical health status, 16.1%, a moderate clinical status and mild physical health, 11.0%; clinical picture and severe physical health. 49.2% of patients who presented infection by Sars-CoV-2 (Covid-19) at the first level of care presented a moderate clinical picture and a moderate current mental health status, 15.3%, a moderate clinical status and health mild mental, 10.2%; clinical picture and severe mental health. 39.0% of patients who presented infection by Sars-CoV-2 (Covid-19) at the first level of care presented a moderate clinical picture and a moderate current social health status, 18.6%, a clinical status and social health mild, 9.3%; clinical picture and severe social health. And, 33.9% of patients who presented Sars-CoV-2 (Covid-19) infection at the first level of care presented a moderate clinical picture and a moderate current health status, 17.8%, a moderate clinical status and health mild current, 7.6%; Severe clinical picture and current health. Conclusions The sequelae of Sars-CoV-2 (Covid-19) infection is information to the initial clinical behavior in patients and their behavior is according to the risk factors or comorbidity they present, therefore it is necessary to implement health strategies in the framework of health promotion to strengthen self-care measures and to avoid complications of the disease.